On the meaning of Cypripedium × grande (Orchidaceae) and its taxonomic history, with a new name for the nothospecies occurring in Costa Rica and Panama - Pupulin, Franco; Díaz-Morales, Melissa (Phytotaxa, 2018)
The taxonomic history of Phragmipedium × grande is traced to show that its current treatment as the cross between P. longifolium and P. humboldtii is untenable. According to our interpretation of the holotype and other materials prepared from specimens of the original cross, the name Phragmipedium × grande, as well as its counterpart, the orchid grex Phragmipedium Grande, have to be treated as the cross between P. longifolium and a species of sect. Phragmipedium from South America. The similarity of the flowers obtained crossing P. longifolium with P. caudatum and with P. warszewiczianum prevents, at this stage, a definitive statement about the original parentage of P. × grande, so it is advisable to treat it as the hybridizer originally stated, a cross of P. longifolium with the pollen of P. caudatum. This nothospecies cannot be formed under natural conditions, as the geographic ranges of the parental species do not overlap. The natural hybrid between Phragmipedium longifolium and P. humboldtii, previously reported from Panama and recorded here for the first time from Costa Rica, is described as P. × talamancanum. Full illustrations of the new nothospecies are provided.